PSYCHOSOCIAL DEVELOPMENT PORTRAYED IN JANE AUSTEN’S EMMA - Ali Sabri Abuhassan; Mohd Nazri Latiff Azmi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
This paper investigates the bildungsroman phenomenon as depicted in Jane Austen’s Emma (1817) by consulting Erik Erikson’s theory of psychosocial development as a framework of analysis. The most two conflicting readings in this regard could be best seen in Buckley’s (1974) claim which excluded Emma from the bildungsroman, for the genre has always been associated with the protagonist’s physical quest seeking maturity and social integration. However, Kohn (1995) read Emma as a domestic bildungsroman when he argued that Emma did not have to travel physical distances to achieve her maturity. For Kohn, Emma matured within her social sphere. This paper particularly traced Emma’s psychological and social development since this type of development is the basic ingredient of any bildungsroman novel. This paper argued that Emma cannot be read as bildungsroman not because the protagonist did set on a quest, as Buckley claimed, but mainly because Emma did not develop a sense of psychological or social maturation. After placing Emma in Erikson’s developmental stages, the study revealed that she did not really mature neither she realized her own identity. This paper proposed that Emma should not be classified as bildungsroman because the heroine distorted the real meaning of maturity and social integrity.